Análisis espacial y medioambiental de la inmigración en el municipio de Madrid. - Alcolea Moratilla, Miguel Ángel (Observatorio Medioambiental, 2000)
Immigration is a very fairly recent demographic process in our country, which we have to get used. The arrival of foreign population to our cities, is caused by the economic and social condition of their countries of origins most of them be longing to the word and the loon in ours, that motivates that pro 53 Miguel Ángel Alcolea Moratilla Análisis espacial y medio ambiental... cess. It means a human group, that necessarily his to integrate and settle down, although the latter fact does ant always take place, with the subsequent social problems. In this case, we have Madrid, that has seen in increase in the number of foreigners among its citizens, inhabiting part of country house --derelist-- occasions making up homogeneous urban spaces, which can be defined as ghettos. This paper gather, the distribution and the features of the foreigners amongst the districts and neighbourhoods in Madrid.
Keywords: Madrid; district; neighbourhood; immigration; foreign population; «Third Word»; «First Word»; derelict; horsing